1999
DOI: 10.1046/j.1439-0434.1999.00433.x
|View full text |Cite
|
Sign up to set email alerts
|

Fusarium Head Blight Reactions and Accumulation of Deoxynivalenol (DON) and Some of its Derivatives in Kernels of Wheat, Triticale and Rye

Abstract: Fifty‐three commercially grown cultivars and germplasm lines of winter triticale (n = 18), wheat (n = 13), and rye (n = 5) and spring triticale (n = 8), wheat (n = 7) and rye (n = 2) were inoculated at mid anthesis with a spore suspension consisting of a mixture of Fusarium culmorum, Fusarium avenaceum and Fusarium graminearum isolates of known toxinogenic activity. Reactions to Fusarium head blight were measured as disease severity, reductions of kernel number/head, kernel weight/head and 1000 kernel weight, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
36
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 0 publications
8
36
0
1
Order By: Relevance
“…Lemmens et al (2004) found out that good correlations between AUDPC and DON content are present at low to intermediate disease levels. Both FDG and reduction in thousand grain weight reflecting the kernel infection can be considered valuable traits (Šíp et al 2002), but FDG is more frequently used as an indicator of FHB resistance (Arseniuk et al 1999;Ittu et al 2000;Wiśniewska et al 2002;Lemmens et al 2003;Mesterházy et al 2005). A new method for the evaluation of FHB infection with respect to the plant phenological stage called REML (a statistical method using a mixed model) was recently published by Emrich et al (2008) in order to avoid an unintended selection for late-heading genotypes when evaluating FHB infection in wheat.…”
Section: Methods For Evaluation Of Fhb Resistance In Small Grain Cerementioning
confidence: 99%
“…Lemmens et al (2004) found out that good correlations between AUDPC and DON content are present at low to intermediate disease levels. Both FDG and reduction in thousand grain weight reflecting the kernel infection can be considered valuable traits (Šíp et al 2002), but FDG is more frequently used as an indicator of FHB resistance (Arseniuk et al 1999;Ittu et al 2000;Wiśniewska et al 2002;Lemmens et al 2003;Mesterházy et al 2005). A new method for the evaluation of FHB infection with respect to the plant phenological stage called REML (a statistical method using a mixed model) was recently published by Emrich et al (2008) in order to avoid an unintended selection for late-heading genotypes when evaluating FHB infection in wheat.…”
Section: Methods For Evaluation Of Fhb Resistance In Small Grain Cerementioning
confidence: 99%
“…It was shown in different experiments (e.g. Arseniuk et al 1999;Ittu et al 2000;Lemmens et al 2003;Šíp et al 2007) that particularly the determination of the percentage of Fusarium damaged grains (FDG) appeared to be useful from these aspects. Close correlations between DON content and FDG were also revealed in the experiments of Mesterházy et al (2005), however, this research demonstrated the importance of measuring both FDG and DON in the breeding and selection of resistant germplasm and varieties.…”
mentioning
confidence: 99%
“…The cultivars with total resistance to FHB are not avaiable, but the significant differences between cultivars existes. There were found out the differencies in FHB in Slovakia (Šrobárová & Vašková 1987) and in mycotoxin DON production (Arseniuk et al 1999;Mesterházy et al 1999;Perkowski et al 2002). We have confirmed the obtained results also among Slovakian cultivars in experiments for both types of resistance.…”
Section: Discussionmentioning
confidence: 99%